1986
DOI: 10.4315/0362-028x-49.10.768
|View full text |Cite
|
Sign up to set email alerts
|

Method to Isolate Escherichia coli O157:H7 from Food

Abstract: A medium for direct overnight isolation of hemorrhagic colitis (HC) strains of Escherichia coli from foods has been developed. It is a direct plating medium incorporating tryptophan (as tryptone), sorbitol, an indicator dye and a fluorogenic substrate for diagnostic purposes. Sodium chloride is included to raise the upper temperature limit for growth and a bile salt concentration lower than that usual for E. coli media but still inhibitory to non-enteric organisms is used. Colonies of HC strains grown overnigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 0 publications
1
37
0
3
Order By: Relevance
“…Previous studies have used EC and mEC medium supplemented with novobiocin for the detection of E. coli O157 from foods (Szabo et al 1986;Bennett et al 1995;Hara-Kudo et al 1999). To detect E. coli O26 and O157 in foods, HaraKudo et al (2000) reported that enrichment in mEC + n at 42°C for 18 h was a successful combination.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used EC and mEC medium supplemented with novobiocin for the detection of E. coli O157 from foods (Szabo et al 1986;Bennett et al 1995;Hara-Kudo et al 1999). To detect E. coli O26 and O157 in foods, HaraKudo et al (2000) reported that enrichment in mEC + n at 42°C for 18 h was a successful combination.…”
Section: Discussionmentioning
confidence: 99%
“…The prefiltrate was decimally diluted in PT, and appropriate dilutions (typically 10 Ϫ1 and 10 Ϫ2 of the prefiltrate) were filtered onto hydrophobic grid membrane filters (HGMFs) (Isogrid membranes; Neogen, Lansing, MI) using a spreadfilter (Filtaflex, Almonte, ON, Canada) and a vacuum manifold. HGMFs were incubated at 37°C face up on hemorrhagic colitis agar (50), modified from the original formulation, to detect all STEC bacteria by the omission of 4-methylumbelliferyl-␤-D-glucuronide (MUG), 1% cefsulodin, and 0.1% potassium tellurite, as these supplements were specific to the isolation of the O157:H7 serotype. Colonies on each HGMF were replicated onto another HGMF using an HGMF replicator/inoculator system (Filtaflex).…”
Section: Methodsmentioning
confidence: 99%
“…by using a spread filter (Filtaflex Ltd., Almonte, Ontario, Canada). The filters were placed on modified hemorrhagic colitis (mHC) agar (44) and incubated overnight at 37°C. One replica of the colonies on the HGMF was placed onto another HGMF with a replicator (Filtaflex Ltd).…”
Section: Detection Of Vt Genes and Isolation Of Vtec From Fecal Samplesmentioning
confidence: 99%